Concomitant Transapical Aortic/Mitral Transcatheter Valve Replacement for Severe Aortic Stenosis and Mitral Annular Calcification - Alicja Zientara, MD; Alison Duncan, MB, BS, PhD; Ee Ling Heng, MBBS, BS, PhD; Cesare Quarto, MD, PhD (JACC: Case Reports, 2023)
Mitral regurgitation (MR) associated with mitral annular calcification (MAC) is surgically challenging, and valve-in-MAC procedures using transcatheter aortic valve replacement (TAVR) devices have poor outcomes. Transcatheter mitral valve replacement (TMVR) may be an option. Concomitant TAVR and TMVR are limited to 2 reports. We describe the first case of concomitant TAVR and TMVR-in-MAC procedures. (Level of Difficulty: Advanced.)